(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
In this article, future professionals study independently in relation to their abilities, talents, opportunities, interests, future professionals learn to develop students’ cognitive abilities, study aspects that need to be taken into account taking into account students’ independent learning activities, the innovative activity of future specialists is widely highlighted the ways of development, the role and importance of forming students’ creative abilities in the process self-study.